The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1177/0748233711422735
|View full text |Cite
|
Sign up to set email alerts
|

Occupational genotoxicity among copper smelters

Abstract: Occupational exposure in a copper smelting industry may produce various adverse health effects including cancer. Despite a number of well-documented studies reporting an increased risk of cancer among copper smelter workers, the data on genotoxic effects in this industry are scarce. In view of the above, an assessment of DNA damage in peripheral blood leukocytes by Comet assay from copper smelter workers was undertaken. Additionally, the proton-induced X-ray emission (PIXE) analysis was assessed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…Levengood and Heske (2008) did not detect any changes in the reproductive activity of small mammals from areas contaminated with copper and zinc. Nevertheless, copper does accumulate in different tissues (Appleton et al 2000;Martiniakova et al 2010Martiniakova et al , 2011Martiniakova et al , 2012 and can cause DNA damage (Yamashita et al 1998;Linder 2001;De Olivera et al 2012). In view of this, in further studies we will examine the impact of copper intake on offspring, and specifically its accumulation in different tissues and its effect on sexual maturation.…”
Section: Discussionmentioning
confidence: 96%
“…Levengood and Heske (2008) did not detect any changes in the reproductive activity of small mammals from areas contaminated with copper and zinc. Nevertheless, copper does accumulate in different tissues (Appleton et al 2000;Martiniakova et al 2010Martiniakova et al , 2011Martiniakova et al , 2012 and can cause DNA damage (Yamashita et al 1998;Linder 2001;De Olivera et al 2012). In view of this, in further studies we will examine the impact of copper intake on offspring, and specifically its accumulation in different tissues and its effect on sexual maturation.…”
Section: Discussionmentioning
confidence: 96%
“…34,35 De Olivera, et al , showed a significant increase in DNA damage in peripheral blood lymphocytes of smelter workers compared to the controls. 15…”
Section: Discussionmentioning
confidence: 99%
“…From a previous report, the mean DNA damage for copper smelters and controls differed by 13.0 (damage index/100 leukocytes). 15 To detect a difference of this magnitude, considering a SD of 10.0, type I error of 0.05, and study power of 90%, the minimum sample size for each group (case and the comparison group) was calculated to be 22. To ascertain normalcy of data, we decided to study at least 30 cases and 30 controls.…”
Section: Methodsmentioning
confidence: 99%
“…Copper. Occupational exposure to copper (Cu) has been reported to result in chromosome aberrations and increased frequency of micronuclei in peripheral blood leukocytes (48) . In addition to genomic toxicity, Cu can also alter the epigenome.…”
Section: Metal Exposure and Associated Epigenetic Alterationsmentioning
confidence: 99%